Visible multi-color electrochromism by tailor-made color mixing at one electrode. (7th September 2020) - Kayaba, Yuki; Hojo, Kenta; Ono, Kenta; Ishizaki, Manabu; Kanaizuka, Katsuhiko; Kondo, Shin-ichi; Kurihara, Masato; Mitsuishi, Masaya; Matsui, Jun
Abstract: Visible multi-color electrochromism has been achieved by mixing two colors at one working electrode using a hetero-multilayer layer-by-layer (LbL) film. The hetero-multilayer LbL film consists of a redox-conductive layer-by-layer (LbL) film (inner layer) and an electrochromic LbL film (outer layer). The redox-conductive film was constructed by LbL deposition of a cationic copolymer that contains ruthenium complexes and sodium polyacrylate, whereas the electrochromic LbL film was fabricated using Prussian blue (PB) nanoparticles and poly(ethylene imine). The cyclic voltammogram of the hetero-multilayer film suggested that PB is located at two different sites. This difference in location enables controlling each PB redox reaction independently. As a result, the film exhibited visible electrochromic colors of conventional PB, that is blue due to the predominant presence of PB and yellow upon oxidizing PB to Prussian yellow (PY), as well as green for a mixture of PB and PY, even only one working electrode is used.